Management of Biological Nitrogen Fixation for the Development of More Productive and Sustainable Agricultural Systems 1995
DOI: 10.1007/978-94-011-0053-3_2
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable agriculture in the semi-arid tropics through biological nitrogen fixation in grain legumes

Abstract: Sustainable agriculture relies greatly on renewable resources like biologically fixed nitrogen. Biological nitrogen fixation plays an important role in maintaining soil fertility. However, as BNF is dependent upon physical, environmental, nutritional and biological factors, mere inclusion of any Nrfixing plant system does not guarantee increased contributions to the soil N pool. In the SAT where plant stover is also removed to feed animals, most legumes might be expected to deplete soil N. Yet beneficial legum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Soybeans fix nitrogen from the air via a symbiotic relationship with Rhizobium bacteria. The process will increase the mineral soil nitrogen content, in the other hand, it also benefit for neighboring plants (Kuepper et al 2001;Cheng 1994;Wani et al 1995;Vance 1998). The results in this paper showed that the change of total nitrogen content of mineral soil in ash/soybean intercropping system was more significant than that in larch/soybean intercropping system.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Soybeans fix nitrogen from the air via a symbiotic relationship with Rhizobium bacteria. The process will increase the mineral soil nitrogen content, in the other hand, it also benefit for neighboring plants (Kuepper et al 2001;Cheng 1994;Wani et al 1995;Vance 1998). The results in this paper showed that the change of total nitrogen content of mineral soil in ash/soybean intercropping system was more significant than that in larch/soybean intercropping system.…”
Section: Discussionmentioning
confidence: 97%
“…Planting crop was soybean. It is well known that leguminous plants can give benefits to the soil, such as improving nutrient availability, improving the structure of soil, reducing pest and disease incidence and hormonal effects through rhyzodeposition (Wani et al 1995). The major benefit of leguminous plants comes from biologically fixed N 2 of symbiosis, involving leguminous plants and bacterial diazotrophs (Vance 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The %Ndfa values for the crop legume symbioses in Table 2 were sourced from Peoples et al (2008) in which data from a number of reviews and experimental papers were summarised (Peoples and Craswell 1992;Herridge and Danso 1995;Peoples et al 1995;Wani et al 1995;Jensen 1997;Unkovich et al 1997;Schulz et al 1999;Unkovich and Pate 2000;Giller 2001;Rochester et al 2001;Turpin et al 2002;Aslam et al 2003;Shah et al 2003). Additional information on N 2 fixation of common bean was sourced from Rennie and Kemp (1982a, b) and .…”
Section: Crop Legumes-rhizobiamentioning
confidence: 99%